Analysis of the Impact of Information Technologies for Making Management Decisions, Including Project Ones - Ziuziun, Vadym (International Electronic Scientific and Practical Journal «WayScience», 2023)
This paper analyzes the impact of information technologies (IT) on management decision-making and project evaluation. It highlights that no single approach is sufficient to justify an IT project, emphasizing the need for tailored methodologies and system-driven evaluation indicators. The study examines key parameters of the IT Performance Index alongside the direct effects of IT on productivity, risk management, and decision quality. A quantitative evaluation model based on the ratio of results to costs is presented, detailing implementation expenses and labor cost savings. Finally, a adapted net present value (NPV) formula is utilized to account for future uncertainties and demonstrate the overall economic value of IT projects.
Keywords: information technology; management decisions; project evaluation; economic efficiency; net present value